2018
DOI: 10.1212/wnl.0000000000004773
|View full text |Cite
|
Sign up to set email alerts
|

Neurofascin antibodies in autoimmune, genetic, and idiopathic neuropathies

Abstract: ObjectiveTo measure the frequency, persistence, isoform specificity, and clinical correlates of neurofascin antibodies in patients with peripheral neuropathies.MethodsWe studied cohorts of patients with Guillain-Barre syndrome (GBS) or chronic inflammatory demyelinating polyneuropathy (CIDP) (n = 59), genetic neuropathy (n = 111), and idiopathic neuropathy (n = 43) for immunoglobulin (Ig) G and IgM responses to 3 neurofascin (NF) isoforms (NF140, NF155, and NF186) using cell-based assays.ResultsNeurofascin ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 22 publications
14
88
3
1
Order By: Relevance
“…In contrast to a recent study also describing anti-neurofascin-155 IgM,7 we did not detect any IgM autoantibodies in patients with non-inflammatory neuropathies and thus found a significant difference of autoantibody frequency between inflammatory neuropathies and controls. This supports the idea of a pathogenic or at least disease-associated role of IgM autoantibodies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a recent study also describing anti-neurofascin-155 IgM,7 we did not detect any IgM autoantibodies in patients with non-inflammatory neuropathies and thus found a significant difference of autoantibody frequency between inflammatory neuropathies and controls. This supports the idea of a pathogenic or at least disease-associated role of IgM autoantibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…A patient with a combination of IgM, IgA and IgG3 anti-neurofascin-155 autoantibodies has been reported,4 but subsequent studies focused on the detection of IgG autoantibodies. Only recently a cohort of patients with inflammatory and non-inflammatory neuropathies was published that had been screened for anti-neurofascin IgM and IgG by cell-based assays 7. These authors found IgM autoantibodies in 8% of patients with inflammatory neuropathy, but also in 5% of patients with idiopathic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient manifested a severe clinical phenotype very similar to those typical of anti‐NF‐155 antibody–associated CIDP. A GBS‐like onset of the disease, as well as good responses to rituximab, have also been reported. However, the heterogeneity in clinical severity and phenotypes (e.g., disabling tremor was absent in some cases) makes the comparative evaluations of rituximab efficacy difficult.…”
supporting
confidence: 67%
“…IgG3 antibodies against all 3 neurofascin isoforms were detected in 3 cases presenting with a fulminant neuropathy with tetraplegia and cranial nerve palsy, and with respiratory failure and autonomic involvement in 2 of these . Similar findings were observed in 2 patients with pan‐neurofascin IgG3 antibodies, but also in 2 patients with IgG4 antibodies . The latter suggests that the unique clinical picture may be mostly explained by a unique epitope, a common domain of nodal NF140/186 and paranodal NF155, but may also be associated with the IgG3 subclass.…”
Section: Chronic Neuropathies Associated With Igg4 Antibodies Againstsupporting
confidence: 76%